Antibacterial Effect of Pulsatilla chinensis towards Staphylococcus aureus, Shigella dysenteriae, and Salmonella typhi - Fong, Sim Chee; Mulyana, Yanti; Girawan, Dolvy (Althea Medical Journal, 2016)
Background: Pulsatilla (P.) chinensis is a kind of traditional Chinese medicine (TCM) that has antibacterial effect. It is used to treat diarrhea, dysentery, and other diseases. The P. chinensis is composed of some potent antibacterial substances including protoanemonin, saponin, oleanolic acid. The study aimed to determine the antibacterial effect of P. chinensis towards staphlococcus aureus, Shigella dysenteriae, and Salmonella typhi.Methods: This was an experimental descriptive study that was conducted in 2014 using two methods, diffusion and dilution method. In diffusion method, 5 holes were made on the agar that bacteria were growing and different concentrations of P. chinensis infusion were placed in different hole. The inhibitory effect was measured by the inhibition zone. In dilution method, 8 test tubes with decreasing concentration of P. chinensis infusion were mixed with the bacteria suspension and Mueller Hinton Solution. The minimal inhibitory concentration (MIC) was measured by the last clear test tube. The test tube with solution that showed absence of bacteria on culture indicated the minimal bactericidal concentration (MBC).Results: In diffusion method, P. chinensis infusion showed inhibitory effect towards S. aureus and bacteriostatic effect towards S. dysenteriae and S. typhi. In dilution method, there was no antibacterial activity detected.Conclusions: P. chinensis infusion has inhibitory effect on S. aureus and bacteriostatic effect on S. dysenteriae and S. typhi. [AMJ.2016;3(2):292â5]DOI:Â 10.15850/amj.v3n2.467